Supplementation of Specific Collagen Peptides Following High-Load Resistance Exercise Upregulates Gene Expression in Pathways Involved in Skeletal Muscle Signal Transduction - Centner, Christoph; Jerger, Simon; Mallard, Alistair; Herrmann, Anna; Varfolomeeva, Eugenia; Gollhofer, Sandra; Oesser, Steffen; Sticht, Carsten; Gretz, Norbert; Aagaard, Per; Nielsen, Jakob L.; Frandsen, Ulrik; et al. (Frontiers in Physiology, 2022)
Previous evidence suggests that resistance training in combination with specific collagen peptides (CP) improves adaptive responses of the muscular apparatus. Although beneficial effects have been repeatedly demonstrated, the underlying mechanisms are not well understood. Therefore, the primary objective of the present randomized trial was to elucidate differences in gene expression pathways related to skeletal muscle signal transduction following acute high-load resistance exercise with and without CP intake. Recreationally active male participants were equally randomized to high-load leg extension exercise in combination with 15g CP or placebo (PLA) supplementation. Muscle biopsies from the vastus lateralis muscle were obtained at baseline as well as 1h, 4h and 24h post exercise to investigate gene expression using next generation sequencing analysis. Several important anabolic pathways including PI3K-Akt and MAPK pathways were significantly upregulated at 1h and 4h post-exercise. Significant between-group differences for both pathways were identified at the 4h time point demonstrating a more pronounced effect after CP intake. Gene expression related to the mTOR pathway demonstrated a higher visual increase in the CP group compared to PLA by trend, but failed to achieve statistically significant group differences. The current findings revealed a significantly higher upregulation of key anabolic pathways (PI3K-Akt, MAPK) in human skeletal muscle 4 hours following an acute resistance training combined with intake of 15 g of specific collagen peptides compared to placebo. Further investigations should examine potential relationships between upregulated gene expression and changes in myofibrillar protein synthesis as well as potential long-term effects on anabolic pathways on the protein level.